2013
DOI: 10.3390/foods2040521
|View full text |Cite
|
Sign up to set email alerts
|

Dairy-Based Emulsions: Viscosity Affects Fat Difference Thresholds and Sweetness Perception

Abstract: In complex emulsions, viscosity or viscosity-associated sensory attributes such as creaminess are important for quality assessment and product differentiation. Two sets of emulsions with fat or locust bean gum content being varied at seven levels were developed; the two emulsions at each level had similar apparent viscosity. Additionally, sugar concentration was kept constant either with respect to total emulsion, or with respect to the aqueous phase. Series of two-alternative forced choice tests were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…This confirms what Zahn et al . () suggested. When viscosities differ between samples tasted, the JND is lower than for isoviscous samples.…”
Section: Discussionmentioning
confidence: 96%
“…This confirms what Zahn et al . () suggested. When viscosities differ between samples tasted, the JND is lower than for isoviscous samples.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study reported JNDs for creaminess perception when the apparent viscosity of dairy‐based emulsions varied. Apparent viscosity variations were achieved by differing fat content or locust bean gum content in emulsions (Zahn and others ). Calculated Weber fractions were approximately K = 0.20 (Zahn and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Apparent viscosity variations were achieved by differing fat content or locust bean gum content in emulsions (Zahn and others ). Calculated Weber fractions were approximately K = 0.20 (Zahn and others ). Rohm and Raaber () studied the JNDs and Weber fraction for kinesthetic firmness perception and spreadability perception of edible fats by asking subjects to cut and spread different spreads with a knife (Rohm and Raaber ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that higher-ED milk promotes greater satiety than lower-ED milk. Even though the higher-ED and lower-ED milks were not rated differently in liking and preference, the children may have responded to differences in sensory properties such as viscosity or creaminess (Bakke, Shehan, & Hayes, 2016; Zahn, Hoppert, Ullrich, & Rohm, 2013), which have been shown to influence satiety and fullness (Mattes & Rothacker, 2001; Zijlstra, Mars, de Wijk, Westerterp-Plantenga, & de Graaf, 2008, Camps, et al, 2016). Sensory characteristics may play a more critical role in studies of satiation, such as the present one, than in studies of satiety (Camps, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%